VD_FINDINFO Réc-civile / 2020 / 13 vom 21. Juli 2020 - VD Tribunal cantonal (2020)
RÉCUSATION, PROCÉDÉ TÉMÉRAIRE, COMPÉTENCE | 47 al. 1 let. a CPC (CH), 47 al. 1 let. f CPC (CH), 50 al. 2 CPC (CH), 8a al. 1 CDPJ, 8a al. 3 CDPJ, 8a al. 7 CDPJ